PENENTU-PENENTU PENGGUNAAN E-BANKING PADA PERUSAHAAN-PERUSAHAAN INDONESIA - , MELISSA TRI ANGELA SIMARMATA, Prof. Jogiyanto H. M., M.B.A., Akt., PhD. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to propose one model of the e-banking use by Indonesian companies are influenced by factors perceived benefits, perceived credibility, organizational innovativeness, financial resources, technological resources, government regulations, business partners policy, and the competition intensity. The study was based on the Social Contract Theory, Diffusion of Innovation Theory, Institutional Intervention Theory and Institutional Theory. Samples are intended private companies located in Daerah Istimewa Yogyakarta and obtained as many as 71 companies. Statistical analysis does is test the Validity and Reliability of the initial data, Validity and Reliability Construct test to test the instruments, Normality test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. Multiple Regression Analysis to test the empirical model and hypotheses. The study proposed eight alternative hyphotesis and the results show that perceived benefits and technological resources factors is supported. Perceived credibility, organizational innovativeness, business partners policy, financial resources, government regulation and competition density factors is not supported.